2006
DOI: 10.1111/j.1365-2133.2006.07194.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of systemic sclerosis-related digital ulcers and sarcoidosis with endothelin receptor antagonist (bosentan) therapy

Abstract: all specimens: psoriasiform changes were observed in the epidermis (hyperkeratosis and parakeratosis, and absence of granular layer). A superficial lymphocytic and eosinophilic infiltrate was found in the upper dermis. This infiltrate was prominent around the vessels. There were no pathological criteria suggesting cutaneous T-cell lymphoma. Mycological cultures from skin and nails were negative. Serum thyroid hormone levels were normal. Blood testing for arsenic was negative. Chest computed tomographic scan, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…In 2006, there were two published case reports describing the efficacy of bosentan in treating cutaneous ulcerations in sclerodermatous conditions. The first case described a 61-year-old female with limited cutaneous SSc and multiple DU refractory to CCB and IV prostacyclin therapy [37]. After 6 months of standard bosentan therapy (62.5 mg  BID × 4  weeks  then  125 mg  BID), she experienced resolution of her DU correlating with a decrease in plasma ET-1 concentration.…”
Section: Endothelin Receptor Antagonistsmentioning
confidence: 99%
“…In 2006, there were two published case reports describing the efficacy of bosentan in treating cutaneous ulcerations in sclerodermatous conditions. The first case described a 61-year-old female with limited cutaneous SSc and multiple DU refractory to CCB and IV prostacyclin therapy [37]. After 6 months of standard bosentan therapy (62.5 mg  BID × 4  weeks  then  125 mg  BID), she experienced resolution of her DU correlating with a decrease in plasma ET-1 concentration.…”
Section: Endothelin Receptor Antagonistsmentioning
confidence: 99%
“…Of note, the study failed to demonstrate an impact of bosentan on the healing of ulcers, but confirmed its capacity to prevent the development of new digital ulcerations and to induce an improvement in the functionality of the hand and a diminution of pain in treated patients [127]. A small observational study of four patients with SSc-related severe Raynaud's phenomenon and digital ulcers, as well as several other case reports, corroborates the findings of these two extensive, randomized, controlled trials [128][129][130][131][132]. To summarize, the use of bosentan for pulmonary arterial hypertension associated with SSc is encouraged by randomized clinical trials reporting a significant effect on the mortality of these patients and also on their functional capacity, although this is more pronounced for patients with primary pulmonary arterial hypertension.…”
Section: Phosphodiesterase-5 Inhibitorsmentioning
confidence: 56%
“…Bosentan was able to reduce the development of new ulcers in the treatment versus the placebo group by 48% (1.4 vs. 2.7 new ulcers). Although no healing of preexistent ulcers has been observed in the RAPIDS-1 study, several authors reported on cases with a marked improvement of digital ulcers [3,4,5]. In a long-term prospective noncontrolled study, bosentan showed a significant decrease in the number of ulcers [6].…”
Section: Discussionmentioning
confidence: 99%